Implementasi Senam Lansia Sebagai Upaya Preventif Hiperkolesterolemia pada Lansia - Hoesny, Rezkiyah; Rismawati, Rismawati; Santi, Santi; Hoesny, Munafrin; Nursam, Nasrullah (Universitas Methodist Indonesia, 2025)
Hypercholesterolemia is common in the elderly population because it is related to the environment, genetic factors and comorbidities. In all age groups, men and women over 60 years have the highest prevalence of high serum cholesterol levels, high total cholesterol and low-density lipoprotein levels predict the risk of coronary heart disease in patients over 60 years. Preventive efforts that can be made are through early detection to detect hypercholesterolemia in the elderly through Elderly Gymnastics which can affect body balance, improve the physical and psychological health of the elderly, can reduce insomnia and reduce symptoms of stress and depression. Community service carried out at the Bilante Village Posyandu, the working area of ​​the Larompong Health Center, Luwu Regency, South Sulawesi Province, was successfully implemented. This activity was carried out by examining the blood cholesterol levels of the elderly pre-post elderly gymnastics, followed by elderly gymnastics which was carried out once a week for four consecutive weeks. Elderly gymnastics has been shown to reduce hypercholesterolemia if done for 30-60 minutes each time. Routine cholesterol checks and elderly exercise can increase the elderly's knowledge about hypercholesterolemia and they can adapt to healthy living behaviors. Elderly people who maintain their physical condition well and feel comfortable in living their lives will have an impact on the quality of life of the elderly.